Assessing educational unfair inequalities at a regional level in Colombia (2015)
This document aims to provide evidence regarding the existence of different patterns in equality of opportunities in academic achievement during the last fifteen years in Colombia. The outcomes selected for measuring inequality are the scores obtained on the national test Saber 11 in math as well as reading. It is found that inequality has increased during this period, and that this trend is common for all the metropolitan areas included in the analysis. Most of the increase found comes from factors related to the school market. It is found that inequality of opportunities is higher than 20% in almost all the studied areas. © 2015 Universidad de Antioquia. All rights reserved.